Electron beam photoresist composition containing self-crosslinking resin as well as preparation method and application of electron beam photoresist composition
By doping self-crosslinked resin in electron beam photoresist, the problem of pattern lines prone to collapse is solved, the roughness and adhesion of line edges is improved, and the demand for high resolution in large integrated circuits and display industries is met.
Patent Information
- Application Number
- CN202411374332.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The problem that existing electron beam photoresist is prone to collapse in pattern lines leads to high production costs and low resolution, making it difficult to meet the needs of large integrated circuits and display industries for higher resolution.
Doping self-crosslinking resin in the electron beam photoresist base resin, the crosslinking polymer is formed by reacting the chain polymer with the crosslinking agent, enhancing the adhesion of the resin and improving line stability.
Without affecting resolution and corrosion resistance, the problem of easy collapse of electron beam lithography pattern lines is significantly improved, the roughness of line edges is improved, and the production cost is reduced.
Smart Images

Figure CN119179230A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photoresists, in particular to an electron beam photoresist composition containing a self-crosslinking resin polymer material and a preparation method and application thereof. Background Art
[0002] Photoresist is a crucial core material in the photolithography process. It is also called photoresist. It refers to an etch-resistant material whose solubility changes after being irradiated or radiated by electromagnetic waves such as ultraviolet light, X-rays and electron beams. It plays the role of transferring patterns and can be widely used in fine graphics processing fields such as displays, integrated circuits, micro-electromechanical systems (MEMS) and optoelectronic devices. In recent years, the rapid development of large-scale integrated circuits and display industries has put forward higher requirements for photolithography technology: obtaining more refined and higher-resolution replica patterns. The development of photolithography technology and the continuous innovation of photolithography materials have jointly promoted the extension of Moore's Law. As predicted by Moore's Law, the critical dimension (CD) representing the level of chip production has continued to decline, resulting in the need to improve photoresist indicators such as line edge roughness and sensitivity. The size of CD is usually determined by the Rayleigh formula. The common strategy to achieve a smaller CD is to reduce the wavelength of the exposure light source. Therefore, the exposure wavelength of the lithography machine is also constantly evolving from ultraviolet g-line (436nm) → i-line (365nm) → 248nm → 193nm → extreme ultraviolet light (EUV) → X-ray, and even non-optical lithography (electron beam exposure, ion beam exposure) is used. The comprehensive performance of photoresist products must also be improved accordingly to meet the requirements of integrated process technology.
[0003] Electron beam photoresist is widely used in the fields of micro-nano pattern preparation, chip design, mask manufacturing, second-generation / third-generation compound semiconductor chip manufacturing, optical communication chip manufacturing, etc. Electron beam photoresist is a type of photolithography material that is coated on the surface of the substrate and realizes pattern transfer through electron beam exposure. Electron beam photoresist is synthesized by combining the respective advantages of benzene ring structure and acrylate resin to obtain a resin molecule with a special structure, and obtains a photoresist resin with excellent performance. At the same time, the process parameters are controlled to obtain a resin product with stable molecular weight and molecular weight distribution, ensuring product quality and stable performance. Finally, the resin, various additives and other ingredients are used to prepare electron beam photoresists with different excellent properties. At present, the electron beam photoresist commonly used in the large-scale integrated circuit industry is mainly polymethyl methacrylate (PMMA) positive photoresist, which has a higher resolution. However, due to its low sensitivity, the required exposure time and production cycle are longer, which also makes its production cost higher. The modified electron beam photoresist, such as ZEP520, is a non-chemically amplified positive chain-breaking electron beam photoresist with high resolution. Its resolution can reach 10 nanometers. Under relatively good process conditions, it can also achieve a graphic structure of 10 to 50 nanometers. It has high sensitivity and good resistance to dry etching. It is composed of a copolymer of α-chloromethyl acrylate and α-methyl styrene. It is a modified polymer of PMMA with benzene rings, and its plasma etching resistance is greatly improved. ZEP520 and PMMA also have high contrast, simple use and good repeatability. Compared with PMMA, the advantage of ZEP520 is that the required dose is relatively small, that is, the sensitivity is higher. Its disadvantage is that the adhesion to the substrate is poor, which leads to the problem of line pattern collapse. Before coating, it may be necessary to heat treat the substrate substrate or use HMDS adhesion promoter bottom layer. Summary of the invention
[0004] To solve the above problems, the present invention provides an electron beam photoresist composition containing a cross-linked resin and a preparation method and application thereof. The electron beam photoresist composition of the present invention comprises a blend of two different system resins, which is doped with a self-cross-linking resin material on the basis of the electron beam photoresist base resin, thereby improving the problem of easy collapse of lines without affecting the basic process of later electron beam lithography.
[0005] The technical solution of the present invention is as follows:
[0006] An electron beam photoresist composition, comprising: an electron beam photoresist base resin material and a self-crosslinking resin;
[0007] The self-crosslinking resin is obtained by reacting a chain polymer with a crosslinking agent; the chain polymer includes an aromatic group and a nitrogen-containing heterocyclic group. The self-crosslinking resin is a crosslinking polymer.
[0008] According to an embodiment of the present invention, the aromatic group and the nitrogen-containing heterocyclic group are both located on the main chain of the chain polymer.
[0009] According to an embodiment of the present invention, the chain polymer is a polyester-based polymer.
[0010] According to an embodiment of the present invention, the chain polymer is formed by polymerizing at least one compound containing an aromatic group and at least one compound containing a nitrogen-containing heterocycle. For example, the chain polymer is formed by polymerizing a compound containing an aromatic group and two compounds containing nitrogen-containing heterocycles.
[0011] According to an embodiment of the present invention, in the chain polymer, the polymerized units are linked through ester bonds to form the polymer.
[0012] According to an embodiment of the present invention, the aromatic group may be a monocyclic or polycyclic aromatic or heteroaromatic group, for example, C 6-20 Aryl, 5-20 membered heteroaryl; preferably C 6-14 Aryl, 5-14 membered heteroaryl, for example, phenyl, naphthyl, anthracenyl or biphenyl.
[0013] According to an embodiment of the present invention, the compound containing an aromatic group further comprises a carboxyl group, a carboxylate group (such as COOC 1-12 alkyl), a carboxylic anhydride group, or a hydroxyl group.
[0014] According to an embodiment of the present invention, the compound containing an aromatic group further comprises at least two groups selected from carboxylic acid, carboxylic acid ester, carboxylic acid anhydride, and / or at least two hydroxyl groups.
[0015] In some embodiments of the present invention, the compound containing an aromatic group has a structure shown as follows M1':
[0016] ROOC-A-COOR
[0017] M1'
[0018] Wherein, A is selected from the following groups which are unsubstituted or optionally substituted by one, two or more Rs: C 6-20 Aryl, 5-20 membered heteroaryl, C 6-20 Aryl-C 6-20 Aryl or 5-20 membered heteroaryl-5-20 membered heteroaryl; Rs is selected from oxo, halogen, cyano, nitro, C 1-12 Alkyl, C 1-12 Alkoxy, C 3-12 Cycloalkyl or 3-12 membered heterocyclic group;
[0019] R is selected from C 1-12 alkyl.
[0020] In some embodiments of the present invention, in M1', A is selected from C 6-14 Aryl, 5-14 membered heteroaryl, C 6-14 Aryl-C 6-14 Aryl or 5-14 membered heteroaryl-5-14 membered heteroaryl;
[0021] R is selected from H, C 1-6 alkyl.
[0022] In some specific embodiments of the present invention, the compound containing an aromatic group is, for example, the following compound:
[0023]
[0024] According to an embodiment of the present invention, the compound containing a nitrogen-containing heterocyclic ring further comprises a carboxyl group, a carboxylate group (such as COOC 1-12 alkyl), a carboxylic anhydride group, or a hydroxyl group.
[0025] According to an embodiment of the present invention, the compound containing a nitrogen-containing heterocycle further comprises at least two groups selected from carboxylic acids, carboxylic acid esters, carboxylic acid anhydrides, and / or at least two hydroxyl groups.
[0026] According to an embodiment of the present invention, the compound containing a nitrogen-containing heterocycle is a compound of the following general formula I:
[0027]
[0028] Wherein, R1 and R2 are the same or different and are selected from -C 1-12 Alkyl-OR4, -C 1-12 Alkyl-COOR5, -C 1-12 Alkyl-OCOR5; R3 is selected from -C 1-12 Alkyl-OR4, -C 1-12 Alkyl-COOR5, -C 1-12 Alkyl-OCOR5, R6;
[0029] R4, R5, R6 are the same or different and are selected from H, optionally replaced by one or more R a Substituted with the following groups: C 1-12 Alkyl, C 2-12 Alkenyl, C 2-12 Alkynyl, aryl, heteroaryl;
[0030] R a are the same or different and are selected from oxo, halogen, cyano, nitro, alkyl, cycloalkyl, heterocyclyl, aryl, heteroaryl, -NR b R c 、-OR d 、-CO-Rd 、-COOR d 、-SR e 、-SO-R e 、-SO2-R e ;
[0031] R b , R c same or different, independently selected from hydrogen or optionally replaced by one, two or more R a Substituted with the following groups: C 1-12 Alkyl, C 3-12 Cycloalkyl;
[0032] R d , R e The same or different, independently selected from H, or optionally replaced by one, two or more R a Substituted with the following groups: C 1-12 Alkyl, C 3-12 Cycloalkyl, 3-12 membered heterocyclic group.
[0033] In some specific embodiments of the present invention, the compound containing a nitrogen-containing heterocycle includes the compounds shown in the following M2' and M3':
[0034]
[0035] Among them, R 21 , R 22 , R 23 The same or different, independently selected from -C 1-12 Alkyl-OH; R 31 , R 32 The same or different, independently selected from -C 1-12 Alkyl-COOH or -C 1-12 Alkyl-COOC 1-12 Alkyl; R 33 Selected from H, C 1-12 Alkyl, aryl, heteroaryl, -C 1-12 Alkyl-OH, -C 1-12 Alkyl-OC 1-12 Alkyl, -C 1-12 Alkyl-COOH or -C 1-12 Alkyl-COOC 1-12 alkyl.
[0036] In some embodiments of the present invention, R 21 , R 22 , R 23 The same or different, independently selected from -C 1-6 Alkyl-OH; R 31 , R 32The same or different, independently selected from -C 1-6 Alkyl-COOH or -C 1-6 Alkyl-COOC 1-6 Alkyl; R 33 Selected from H, C 1-6 Alkyl, -C 1-6 Alkyl-OH, -C 1-6 Alkyl-OC 1-6 Alkyl, -C 1-6 Alkyl-COOH or -C 1-6 Alkyl-COOC 1-6 alkyl.
[0037] In some specific embodiments of the present invention, the compound containing a nitrogen-containing heterocyclic ring is, for example, tris(2-hydroxyethyl)isocyanurate and tris(2-carboxyethyl)isocyanurate.
[0038] In some embodiments of the present invention, the chain polymer is a polymer obtained by reacting M1', M2' and M3'.
[0039] Furthermore, when R 31 , R 32 , R 33 All three groups are -C 1-12 When alkyl-COOH is used, C 1-12 The fatty alcohol caps the unreacted COOH in monomer M3'.
[0040] The crosslinking agent of the present invention can be a crosslinkable compound having at least two substituents capable of forming crosslinks. The crosslinking agent can be an amino crosslinking agent. For example, a glycoluril-based crosslinking agent, a melamine-based crosslinking agent, a urea-based crosslinking agent, a benzoguanamine-based crosslinking agent, or a phenolic compound having a substituent capable of forming crosslinks such as methylol and methoxymethyl.
[0041] In some embodiments of the present invention, the crosslinking agent may be, for example, methoxymethylated glycoluril or methoxymethylated melamine, such as tetramethoxymethyl glycoluril, tetrabutoxymethyl glycoluril or hexamethoxymethyl melamine. The crosslinking agent may be commercially available. For example, glycoluril-based crosslinking agents sold by American Cyanamide Company under the trade names of Cymel 1170, 1171 and 1172; melamine-based crosslinking agents sold by American Cyanamide Company under the trade names of Cymel 300, 301, 303, 350, 370, 380, 1116 and 1130; urea-based crosslinking agents sold by American Cyanamide Company under the trade names of Powderlink 1174, 1196, Beetle 60, 65 and 80; and benzoguanamine-based crosslinking agents sold by American Cyanamide Company under the trade names of Cymel 1123 and 1125.
[0042] In some embodiments of the present invention, the cross-linking agent has a structure as shown in the following formula IC:
[0043]
[0044] Wherein, s is an integer from 1 to 12;
[0045] R7 and R8 are the same or different and are independently selected from H, C 1-12 Alkyl, C 6-14 Aryl or 5-14 membered heteroaryl;
[0046] R9, R 10 , R 11 , R 12 The same or different, independently selected from C 1-12 alkyl.
[0047] According to an embodiment of the present invention, s is an integer of 1-6, such as 1, 2, 3, 4;
[0048] According to an embodiment of the present invention, R7 and R8 are the same or different and are independently selected from H, C 1-6 Alkyl, phenyl; for example, H, methyl, ethyl, propyl, butyl or phenyl.
[0049] According to an embodiment of the present invention, R9, R 10 , R 11 , R 12 The same or different, independently selected from C 1-6 The alkyl group is, for example, methyl, ethyl, n-propyl or n-butyl.
[0050] In some specific embodiments of the present invention, the cross-linking agent is selected from the following structures:
[0051]
[0052] According to an embodiment of the present invention, the weight average molecular weight of the self-crosslinking resin is 1000-8000, such as 2000-7000, 3000-6000 or 4000-5000.
[0053] According to an embodiment of the present invention, the molecular weight distribution coefficient of the self-crosslinking resin is less than 2.5, such as 1.10-1.25, 1.25-1.50, 1.50-2.00, 2.00-2.04, 2.04-2.08 or 2.08-2.14.
[0054] In some specific embodiments of the present invention, the self-crosslinking resin has the structural units shown below:
[0055]
[0056]
[0057] According to an embodiment of the present invention, the electron beam photoresist base resin material is a copolymer of an aromatic vinyl monomer and an α-halogenated acrylate monomer;
[0058] According to an embodiment of the present invention, the aromatic vinyl monomer is selected from at least one of α-methylstyrene monomer and 4-fluoro-α-methylstyrene monomer.
[0059] According to an embodiment of the present invention, the α-haloacrylate monomer is selected from at least one of α-methyl chloroacrylate monomer, α-ethyl chloroacrylate monomer, α-benzyl chloroacrylate monomer, α-chloroacrylate-1-adamantyl ester monomer, α-chloroacrylate-2,2,3,3,3-pentafluoropropyl monomer, α-chloroacrylate-2,2,3,3,4,4,4-heptafluorobutyl monomer, α-fluoroacrylate methyl monomer, α-fluoroacrylate ethyl monomer, α-fluoroacrylate benzyl ester monomer, α-fluoroacrylate-1-adamantyl ester monomer, α-fluoroacrylate-2,2,3,3,3-pentafluoropropyl monomer and α-chloroacrylate-2,2,3,3,4,4,4-heptafluorobutyl monomer.
[0060] In some specific embodiments of the present invention, the base resin material is a resin material obtained by copolymerization of α-methylstyrene and 2-methyl chloroacrylate as follows:
[0061]
[0062] According to an embodiment of the present invention, the weight average molecular weight of the photoresist base resin material is 20,000-100,000, such as 20,000-50,000, 50,000-56,300, 56,300-58,000, 58,000-68,300, 68,300-69,900, 69,900-75,000 or 75,000-100,000.
[0063] According to an embodiment of the present invention, the molecular weight distribution coefficient of the photoresist base resin material is less than 2.5, such as 1.10-1.25, 1.25-1.50, 1.50-2.00, 2.00-2.04, 2.04-2.08 or 2.08-2.14.
[0064] According to an embodiment of the present invention, the electron beam photoresist composition also includes a solvent; the solvent is selected from at least one of anisole, toluene, xylene, trimethylolbenzene, chlorobenzene, dichlorobenzene, propylene glycol monoacetate, propylene glycol monoethyl ether, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol methyl ethyl ether, butyl acetate, neopentyl acetate, γ-butyrolactone and ethyl lactate, preferably anisole.
[0065] According to an embodiment of the present invention, the electron beam photoresist composition may further include an auxiliary agent, wherein the auxiliary agent is selected from at least one of a surfactant, a photoacid generator, a thermal acid generator, a viscosity controller and a stabilizer.
[0066] According to an embodiment of the present invention, the surfactant includes: a nonionic surfactant, for example, polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether and polyoxyethylene oleyl ether; polyoxyethylene alkyl aryl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; polyoxyethylene polyoxypropylene block copolymers; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan trioleate and sorbitan tristearate; polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate fluorinated surfactants. For example, EF301, EF303, EF352, F171, F173, R-30, R-40, R-30-N, FC430, FC431, AG710, S-382, SC101, SC102 and silicone polymer KP341.
[0067] According to an embodiment of the present invention, the surfactant may be mixed in the photoresist composition as a single species or as a plurality of species.
[0068] According to an embodiment of the present invention, the photoacid generator is selected from at least one of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, (4,8-dihydroxy-1-naphthyl)dimethylsulfonium trifluoromethanesulfonate, (4,7-dihydroxy-1-naphthyl)dimethylsulfonium trifluoromethanesulfonate, (4-methoxynaphthyl)diphenylsulfonium trifluoromethanesulfonate, (4-phenylthiophenyl)diphenylsulfonium trifluoromethanesulfonate, 2-(benzo[d][1,3]dioxolan-5-yl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(2,4-dimethoxyphenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine and 2-[4-(4-methoxyphenyl)phenyl]-4,6-bis(trichloromethyl)-1,3,5-triazine.
[0069] According to an embodiment of the present invention, the viscosity control agent is selected from at least one of butanol, chloroform, ethanol, water, acetonitrile, hexane and isopropanol.
[0070] According to an embodiment of the present invention, the stabilizer is at least one selected from p-benzoquinone, methylhydroquinone, p-hydroxyanisole, 2-tert-butylhydroquinone and 2,5-di-tert-butylhydroquinone.
[0071] According to an embodiment of the present invention, the mass percentages of the components of the electron beam photoresist composition are as follows: 3-15% of photoresist base resin material and self-crosslinking resin, such as 3-7.5% or 7.5-15%; 84.95-96.998% of solvent, such as 84.95-92.488% or 92.488-96.998%; 0.002-0.05% of auxiliary agent, such as 0.003-0.01%.
[0072] According to an embodiment of the present invention, the electron beam photoresist composition includes the following components in percentage by mass: 3 to 15% of a base resin material and a self-crosslinking resin, 0.003 to 0.008% of a surfactant, and 84.95 to 96.998% of a solvent.
[0073] Wherein, the mass ratio of the photoresist base resin material to the self-crosslinking resin is 1:(30-160), for example, 1:(40-120).
[0074] The present invention also provides a method for preparing the electron beam photoresist composition, comprising the following steps: mixing the photoresist base resin material and the self-crosslinking resin to obtain the electron beam photoresist composition.
[0075] According to an embodiment of the present invention, the preparation of the photoresist base resin material comprises the following steps: copolymerizing the aromatic vinyl monomer and the α-halogenated acrylate monomer in the presence of an initiator to obtain the photoresist base resin material.
[0076] According to an embodiment of the present invention, the copolymerization reaction of the aromatic vinyl monomer and the α-halogenated acrylate monomer is carried out in an organic solvent.
[0077] According to an embodiment of the present invention, the copolymerization temperature of the aromatic vinyl monomer and the α-halogenated acrylate monomer is 65 to 90°C, such as 65 to 85°C or 85 to 90°C.
[0078] According to an embodiment of the present invention, the initiator used for the aromatic vinyl monomer and the α-halogenated acrylate monomer is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, methyl azobisisobutyrate, benzoyl peroxide, acetyl peroxide, lauroyl peroxide and tert-butyl peroxide.
[0079] According to an embodiment of the present invention, the method further comprises a process for preparing a self-crosslinking resin, comprising:
[0080] S1. polymerizing a compound containing an aromatic group with a compound containing a nitrogen-containing heterocyclic ring to obtain a chain polymer;
[0081] S2. reacting the chain polymer with a cross-linking agent.
[0082] According to an embodiment of the present invention, the reaction temperature in S1 is 120-180° C., for example, 140-160° C. The reaction time is 1-12 hours.
[0083] According to an embodiment of the present invention, the amount of the crosslinking agent used may be 20% to 60% by weight of the polymer intermediate, such as 30% to 50%.
[0084] The present invention also provides a method for using the electron beam photoresist composition, comprising the following steps: coating the electron beam photoresist composition on a substrate, and sequentially performing pre-baking, exposure, post-baking, development and fixing to obtain a photolithography pattern.
[0085] According to an embodiment of the present invention, the substrate is a silicon wafer.
[0086] According to an embodiment of the present invention, the method of use further includes at least one of the following technical features:
[0087] 1) The pre-baking temperature is 160-200° C., such as 160-170° C., 170-180° C., 180-190° C. or 190-200° C.;
[0088] 2) The pre-baking time is 120 to 240 seconds, such as 120 to 180 seconds or 180 to 240 seconds;
[0089] 3) Exposure energy is 75~425μC / cm 2 ;
[0090] 4) The developer used for development is amyl acetate or a mixture of amyl acetate and isopropyl alcohol; preferably amyl acetate;
[0091] 5) The development time is 50 to 70 seconds, such as 50 to 60 seconds or 60 to 70 seconds;
[0092] 6) The fixing solution used for fixing is isopropyl alcohol;
[0093] 7) The fixing time is 10 to 50 seconds, such as 10 to 30 seconds or 30 to 50 seconds.
[0094] The present invention also provides use of the electron beam photoresist composition in electron beam lithography.
[0095] Beneficial Effects
[0096] The invention provides an electron beam photoresist composition, which contains a self-crosslinking resin, wherein the self-crosslinking resin has a polar group, which can enhance the adhesion of the photoresist to a substrate. The photoresist composition of the invention can significantly improve the problem of easy collapse of electron beam lithography pattern lines without affecting the resolution, corrosion resistance and process tolerance. The obtained pattern has good line edge roughness.
[0097] Definition and explanation of terms
[0098] Unless otherwise defined, all technical and scientific terms herein have the same meaning as commonly understood by one of ordinary skill in the art to which the claimed subject matter belongs.
[0099] "More" means three or more.
[0100] The term "halogen" includes F, Cl, Br or I.
[0101] The term "C 1-12 "Alkyl" is understood to mean a straight-chain or branched saturated monovalent hydrocarbon group having 1 to 12 carbon atoms, preferably "C 1-6 Alkyl". For example, "C 1-6 The term "alkyl" refers to straight-chain and branched alkyl groups having 1, 2, 3, 4, 5, or 6 carbon atoms. The alkyl group is, for example, methyl, ethyl, propyl, butyl, pentyl, hexyl, isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, 2-methylbutyl, 1-methylbutyl, 1-ethylpropyl, 1,2-dimethylpropyl, neopentyl, 1,1-dimethylpropyl, 4-methylpentyl, 3-methylpentyl, 2-methylpentyl, 1-methylpentyl, 2-ethylbutyl, 1-ethylbutyl, 3,3-dimethylbutyl, 2,2-dimethylbutyl, 1,1-dimethylbutyl, 2,3-dimethylbutyl, 1,3-dimethylbutyl, 1,2-dimethylbutyl, or the like or isomers thereof.
[0102] The term "C 1-12 "Alkoxy" is understood to mean -OC 1-12 Alkyl, where C 1-12 Alkyl has the above definition.
[0103] The term "C 6-20 "Aryl" is understood to mean an aromatic monocyclic, bicyclic or tricyclic hydrocarbon ring having 6 to 20 carbon atoms, preferably "C 6-14 The term "C 6-14 The term "aryl" is understood to mean preferably a monovalent aromatic or partially aromatic monocyclic, bicyclic or tricyclic hydrocarbon ring ("C 6-14or a ring having 9 carbon atoms ("C9 aryl"), for example indanyl or indenyl, or a ring having 10 carbon atoms ("C 10 aryl), such as tetrahydronaphthyl, dihydronaphthyl or naphthyl, or a ring having 13 carbon atoms ("C 13 aryl), such as fluorenyl, or a ring having 14 carbon atoms ("C 14 aryl), such as anthracenyl, or a ring having 16 carbon atoms ("C 16 When the C 6-22 When the group is substituted, it may be monosubstituted or polysubstituted. Also, there is no limitation on the substitution position, for example, it may be substituted at the ortho, para or meta position.
[0104] The term "5-20 membered heteroaryl" is understood to include monovalent monocyclic, bicyclic or tricyclic aromatic ring systems having 5 to 20 ring atoms and containing 1 to 5 heteroatoms independently selected from N, O and S, for example "5-14 membered heteroaryl". The term "5-14 membered heteroaryl" is understood to include monovalent monocyclic, bicyclic or tricyclic aromatic ring systems having 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14 ring atoms, in particular 5 or 6 or 9 or 10 carbon atoms, and containing 1 to 5, preferably 1 to 3 heteroatoms independently selected from N, O and S, and, in addition, in each case may be benzo-fused. In particular, the heteroaryl group is selected from thienyl, furanyl, pyrrolyl, oxazolyl, thiazolyl, imidazolyl, pyrazolyl, isoxazolyl, isothiazolyl, oxadiazolyl, triazolyl, thiadiazolyl, thia-4H-pyrazolyl and the like and benzo derivatives thereof, such as benzofuranyl, benzothienyl, benzoxazolyl, benzisoxazolyl, benzimidazolyl, benzotriazolyl, indazolyl, indolyl, isoindolyl and the like; or pyridyl, pyridazinyl, pyrimidinyl, pyrazinyl, triazinyl and the like and benzo derivatives thereof, such as quinolyl, quinazolinyl, isoquinolyl and the like; or azinyl, indolizinyl, purinyl and the like and benzo derivatives thereof; or cinnolinyl, phthalazinyl, quinazolinyl, quinoxalinyl, naphthyridinyl, pteridinyl, carbazolyl, acridinyl, phenazinyl, phenothiazinyl, phenoxazinyl and the like.
[0105] The term "C 3-12 "Cycloalkyl" is understood to mean a saturated, monovalent, monocyclic or bicyclic hydrocarbon ring having 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 carbon atoms. 3-12 The cycloalkyl group may be a monocyclic hydrocarbon group such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl or cyclodecyl, or a bicyclic hydrocarbon group such as a decalin ring.
[0106] The term "3-12 membered heterocyclyl" means a saturated monovalent monocyclic or bicyclic hydrocarbon ring containing 1-5, preferably 1-3 heteroatoms selected from N, O and S. The heterocyclyl may be connected to the rest of the molecule through any one of the carbon atoms or the nitrogen atom (if present). In particular, the heterocyclyl may include, but is not limited to, a 4-membered ring such as azetidinyl, oxetanyl, a 5-membered ring such as tetrahydrofuranyl, dioxolyl, pyrrolidinyl, imidazolidinyl, pyrazolidinyl, pyrrolinyl, or a 6-membered ring such as tetrahydropyranyl, piperidinyl, morpholinyl, dithianyl, thiomorpholinyl, piperazinyl or trithianyl, or a 7-membered ring such as diazepanyl. Optionally, the heterocyclyl may be benzo-fused. The heterocyclic group may be bicyclic, for example but not limited to a 5,5-membered ring, such as a hexahydrocyclopenta[c]pyrrole-2(1H)-yl ring, or a 5,6-membered bicyclic ring, such as a hexahydropyrrolo[1,2-a]pyrazine-2(1H)-yl ring. The ring containing nitrogen atoms may be partially unsaturated, i.e. it may contain one or more double bonds, for example but not limited to 2,5-dihydro-1H-pyrrolyl, 4H-[1,3,4]thiadiazinyl, 4,5-dihydrooxazolyl or 4H-[1,4]thiazinyl, or it may be benzo-fused, for example but not limited to dihydroisoquinolinyl. According to the present invention, the heterocyclic group is non-aromatic. BRIEF DESCRIPTION OF THE DRAWINGS
[0107] Figure 1 The energy of the electron beam photoresist sample in Example 1 is 175 μC / cm 2 (left) and energy of 250μC / cm 2 (Right) Scanning electron microscope image of electron beam photoresist.
[0108] Figure 2 For the electron beam photoresist sample of Example 2, the energy is 175 μC / cm 2 (left) and energy of 250μC / cm 2 (Right) Scanning electron microscope image of electron beam lithography.
[0109] Figure 3 The electron beam photoresist sample of Example 3 is prepared at an energy of 175 μC / cm 2 (left) and energy of 250μC / cm 2 (Right) Scanning electron microscope image of electron beam lithography.
[0110] Figure 4 The electron beam photoresist sample of Example 4 is prepared at an energy of 175 μC / cm 2 (left) and energy of 250μC / cm 2 (Right) Scanning electron microscope image of electron beam lithography.
[0111] Figure 5For the electron beam photoresist sample of Example 5, the energy is 175 μC / cm 2 (left) and energy of 250μC / cm 2 (Right) Scanning electron microscope image of electron beam lithography.
[0112] Figure 6 For the electron beam photoresist samples of Examples 1-5, the energy is 175 μC / cm 2 (left) and energy of 250μC / cm 2 (Right) LER statistics of electron beam lithography patterns. DETAILED DESCRIPTION
[0113] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0114] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0115] Synthesis Example 1
[0116]
[0117] Self-crosslinking resin TJ-1 synthesis steps: 9g of dimethyl 2,6-naphthalene dicarboxylate (M1), 13.0g of tris(2-hydroxyethyl) isocyanurate (M2), 8.6g of tris(2-carboxyethyl) isocyanurate (M3), 0.24g of p-toluenesulfonic acid monohydrate, 5.16g of n-butanol and 14.6g of anisole were added to the reaction flask in no particular order. The reaction flask was heated to 140-160°C and stirred vigorously for 6 hours to react. After the reaction was complete, the anisole and n-butanol in the reaction flask were distilled off. Subsequently, the resulting reactant was diluted with 67.8g of methyl 2-hydroxyisobutyrate and neutralized with triethylamine. 4.09 g of methyl-2-hydroxyisobutyrate and 10.9 g of 1,3,4,6-tetrakis(methoxymethyl)glycoluril (C1) were added to the obtained 19.2 g polymer solution, stirred at 50°C for 3 hours, cooled to room temperature, and neutralized with triethylamine. The obtained reactant was then precipitated, and the obtained precipitate was washed, filtered, and dried to obtain 16 g (M) of polymer TJ-1 resin solid powder. W =3514, M W / Mn=1.888).
[0118] Synthesis Example 2
[0119]
[0120] Self-crosslinking resin TJ-2 synthesis steps: 9g of dimethyl 2,6-naphthalene dicarboxylate, 13.0g of tris(2-hydroxyethyl) isocyanurate, 8.6g of tris(2-carboxyethyl) isocyanurate, 0.24g of p-toluenesulfonic acid monohydrate, 5.16g of n-butanol and 14.6g of anisole are added to the reaction flask in no particular order. The reaction flask is heated to 140-160°C and stirred vigorously for 6 hours to react. After the reaction is complete, the anisole and n-butanol in the reaction flask are distilled off. Subsequently, the resulting reactant is diluted with 66.8g of methyl 2-hydroxyisobutyrate and neutralized with triethylamine. 4.19g of methyl-2-hydroxyisobutyrate and 9.92g of crosslinker C2 are added to the obtained 20.2g polymer solution, stirred for reaction at 50°C for 3 hours, cooled to room temperature, and neutralized with triethylamine. The obtained reactant was then precipitated, and the obtained precipitate was washed, filtered and dried to obtain 16 g (M) of polymer TJ-2 resin solid powder. W =4375,M W / Mn=2.010).
[0121] Synthesis Example 3
[0122]
[0123] Self-crosslinking resin TJ-3 synthesis steps: 9g of dimethyl 2,6-naphthalene dicarboxylate, 13.0g of tris(2-hydroxyethyl) isocyanurate, 8.6g of tris(2-carboxyethyl) isocyanurate, 0.24g of p-toluenesulfonic acid monohydrate, 5.16g of n-butanol and 14.6g of anisole are added to the reaction flask in no particular order. The reaction flask is heated to 140-160°C and stirred vigorously for 6 hours to react. After the reaction is complete, the anisole and n-butanol in the reaction flask are distilled off. Subsequently, the resulting reactant is diluted with 68.2g of methyl 2-hydroxyisobutyrate and neutralized with triethylamine. 4.31g of methyl-2-hydroxyisobutyrate and 12.89g of crosslinker C3 are added to the obtained 18.3g polymer solution, stirred for reaction at 50°C for 3 hours, cooled to room temperature, and neutralized with triethylamine. The obtained reactant was then precipitated, and the obtained precipitate was washed, filtered and dried to obtain 14 g (M) of polymer TJ-3 resin solid powder. W =3345, M W / Mn=1.740).
[0124] Synthesis Example 4
[0125] Preparation method of electron beam matrix polymer resin: 891.60g (4.0mol) of α-methylstyrene monomer and 606.00g (5.2mol) of methyl 2-chloroacrylate monomer are dissolved in 400g of anisole. After the temperature in the reactor is stabilized at 35+ / -1°C, the monomer solution is added to the reactor. After the monomer solution is added, the external temperature is set to 40°C. After the temperature of the solution in the reactor rises to 40+ / -1°C, the initiator solution (anisole solution containing 1.29g of azobisisobutyronitrile) is added to the reactor, and the container is washed twice with 25g of anisole, and the washing liquid is added to the reactor. After the initiator solution is added, the external temperature is set to 60°C. Heat to 85°C. Then add a dioxane solution containing 0.50g of azobisisobutyronitrile, continue to react for 24 hours, cool to room temperature, and finally precipitate, wash, and dry the reaction solution to obtain 400g of resin solid powder. GPC test data: weight average molecular weight 58687, molecular weight distribution 1.91.
[0126] Preparation of electron beam matrix resin photoresist solution TJ-4: Weigh 23g of the above-mentioned resin solid powder and 180g of anisole, add them into a 500mL brown glass bottle in sequence, and place them on a shaker for 1h to fully dissolve; after the dissolution is completed, the mixed solution is circulated and filtered with a 40nm Nuc filter for 24h to finally obtain an electron beam matrix resin photoresist solution TJ-4 with a solid content of 11.06%.
[0127] Stripping test in developer solution
[0128] The samples prepared in Examples 1-5 in Table 1 were spin-coated on a 2-inch silicon wafer at a speed of 3000 rpm for 60 seconds and then baked on a hot plate at 180°C for 1 minute to form a thin film. The film thickness of the film was measured using a film thickness meter, which was recorded as T1. The thin films formed by the samples in each embodiment were immersed in amyl acetate, kept for 30 seconds, and then dried on a glue spreader for 1 minute, and then baked on a hot plate at 100°C for 30 seconds. Finally, the film thickness of the film was measured using a film thickness meter, which was recorded as T2. The stripping rate S = (T1-T2) / T1*100% was obtained by calculation. It can be seen from the data in Table 1 that the stripping rates of the thin films formed in the embodiments are all less than 2%, which has a good anti-stripping effect, indicating that these materials meet the compatibility requirements of electron beam photoresists.
[0129] Table 1. Determination of peeling degree in amyl acetate
[0130]
[0131] Example 1
[0132] An electron beam photoresist is not doped with a self-crosslinking resin. The preparation method is as follows: 2g of the photoresist solution TJ-4 obtained in Synthesis Example 4 is mixed with 0.022g of a surfactant R-40 with a solid content of 1% and 6g of anisole to obtain a solution. After shaking for 12 hours, the solution is filtered with a 0.22-micron polyethylene microporous filter to obtain a clarified filtrate to prepare an electron beam photoresist composition. The prepared electron beam photoresist composition is used according to the following method: the electron beam photoresist is spin-coated on a 2-inch silicon wafer at a spin-coating speed of 3000rpm, and the coating thickness of the electron beam photoresist is 50nm; pre-baked at 180°C for 180s; exposed in an electron beam lithography machine, with an electron beam lithography voltage of 100KV, a current of 100pA, and an exposure energy of 75-425μC / cm 2 ; then post-baked at 90°C for 2 min; developed in developer, the developer was amyl acetate, the developing time was 60 s, fixed with isopropanol for 10 s, and the pattern morphology was observed by scanning electron microscope. Figure 1 , at an exposure energy of 250μC / cm 2 The graphic at the time Figure 1 ,From the figure, it can be seen that there is a clear collapse at the edge of the line.
[0133] Example 2
[0134] An electron beam photoresist is doped with 10% of a self-crosslinking resin (crosslinking agent C1). The preparation method is as follows: 2g of the photoresist solution TJ-4 obtained in Synthesis Example 4 is mixed with 0.0221g of the polymer TJ-1 obtained in Synthesis Example 1, 0.022g of a surfactant R-40 with a solid content of 1wt%, and 6g of anisole to obtain a solution. After being shaken for 12 hours, the solution is filtered with a 0.22 micron polyethylene microporous filter to obtain a clarified filtrate to prepare an electron beam photoresist composition. The prepared electron beam photoresist composition is used according to the following method: the electron beam photoresist is spin-coated on a 2-inch silicon wafer at a spin-coating speed of 3000rpm, and the coating thickness of the electron beam photoresist is 50nm; pre-baked at 180°C for 180s; exposed in an electron beam photolithography machine, with an electron beam photolithography voltage of 100KV, a current of 100pA, and an exposure energy of 75-425μC / cm 2 ; then post-bake at 90°C for 2 minutes; develop in developer, the developer is amyl acetate, the development time is 60 seconds, fix with isopropyl alcohol for 10 seconds, and observe the pattern morphology with scanning electron microscope. At the exposure energy of 250μC / cm 2 The graphic at the time Figure 2 ,As can be seen from the figure, there is basically no collapse of the lines.
[0135] Example 3
[0136] An electron beam photoresist is doped with 20% of a self-crosslinking resin (crosslinking agent C1). The preparation method is as follows: 2g of the photoresist solution TJ-4 obtained in Synthesis Example 4 is mixed with 0.0442g of the polymer TJ-1 obtained in Synthesis Example 1, 0.022g of a surfactant R-40 with a solid content of 1wt%, and 6g of anisole to obtain a solution. After being shaken for 12 hours, the solution is filtered with a 0.22 micron polyethylene microporous filter to obtain a clarified filtrate to prepare an electron beam photoresist composition. The prepared electron beam photoresist is used according to the following method: the electron beam photoresist is spin-coated on a 2-inch silicon wafer at a spin-coating speed of 3000rpm, and the coating thickness of the electron beam photoresist is 50nm; pre-baked at 180°C for 180s; exposed in an electron beam photolithography machine, with an electron beam photolithography voltage of 100KV, a current of 100pA, and an exposure energy of 75-425μC / cm 2 ; then post-bake at 90°C for 2 minutes; develop in developer, the developer is amyl acetate, the development time is 60 seconds, fix with isopropyl alcohol for 10 seconds, and observe the pattern morphology with scanning electron microscope. At the exposure energy of 250μC / cm 2 The graphic at the time Figure 3 ,As can be seen from the figure, there is no collapse of the lines at all.
[0137] Example 4
[0138] An electron beam photoresist is doped with 20% of self-crosslinking resin TJ-2 (crosslinking agent C2). The preparation method is as follows: 2g of photoresist solution TJ-4 obtained in Synthesis Example 4 is mixed with 0.0442g of polymer TJ-2 obtained in Synthesis Example 2, 0.022g of surfactant R-40 with a solid content of 1wt%, and 6g of anisole to obtain a solution. After shaking for 12 hours, the solution is filtered with a 0.22 micron polyethylene microporous filter to obtain a clear filtrate to prepare an electron beam photoresist composition. The prepared electron beam photoresist is used according to the following method: the electron beam photoresist is spin-coated on a 2-inch silicon wafer at a spin-coating speed of 3000rpm, and the coating thickness of the electron beam photoresist is 50nm; pre-baked at 180°C for 180s; exposed in an electron beam lithography machine, with an electron beam lithography voltage of 100KV, a current of 100pA, and an exposure energy of 75-425μC / cm 2 ; then post-bake at 90°C for 2 minutes; develop in developer, the developer is amyl acetate, the development time is 60 seconds, fix with isopropyl alcohol for 10 seconds, and observe the pattern morphology with scanning electron microscope. At the exposure energy of 250μC / cm 2 The graphic at the time Figure 4 ,As can be seen from the figure, there is no collapse of the lines at all.
[0139] Example 5
[0140] An electron beam photoresist is doped with 20% of self-crosslinking resin TJ-3 (crosslinking agent C3). The preparation method is as follows: 2g of photoresist solution TJ-4 obtained in Synthesis Example 4 is mixed with 0.0442g of polymer TJ-3 obtained in Synthesis Example 3, 0.022g of surfactant R-40 with a solid content of 1%wt, and 6g of anisole to obtain a solution. After shaking for 12 hours, the solution is filtered with a 0.22 micron polyethylene microporous filter to obtain a clear filtrate to prepare an electron beam photoresist composition. The prepared electron beam photoresist is used according to the following method: the above electron beam photoresist is spin-coated on a 2-inch silicon wafer, the spin-coating speed is 3000rpm, and the coating thickness of the electron beam photoresist is 50nm; pre-baking at 180°C for 180s; exposing in an electron beam photolithography machine, the electron beam photolithography voltage is 100KV, the current is 100pA, and the exposure energy is 75-425μC / cm 2 ; then post-bake at 90°C for 2 minutes; develop in developer, the developer is amyl acetate, the development time is 60 seconds, fix with isopropyl alcohol for 10 seconds, and observe the pattern morphology with scanning electron microscope. At the exposure energy of 250μC / cm 2 The graphic at the time Figure 5 ,As can be seen from the figure, there is no collapse of the lines at all.
[0141] By comparing the electron microscope images and line edge roughness (LER) test results of Examples 2, 3, 4, and 5 with those of Example 1, it can be seen that when a dense line / groove pattern with a period of 100 nm is designed at a thickness of 50 nm, the introduction of self-crosslinking resin into the electron beam photoresist of Examples 2-5 not only increases the adhesion of the polymer resin to the substrate, but also maintains the basic photolithography process of the original host polymer, improves the problem of easy collapse of lines when using ZEP520 electron beam photoresist, and at lower exposure energy, the line pattern can also be significantly improved by doping with self-crosslinking resin.
[0142] The LER of the photolithographic patterns obtained in Examples 1-5 is as follows: Figure 6 As shown. Figure 6 It can be seen that the line edge roughness of the photolithographic patterns of Examples 2-5 is significantly improved compared with that of Example 1.
[0143] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An electron beam photoresist composition, characterized in that include: Electron beam photoresist base resin material and self-crosslinking resin; The self-crosslinking resin is obtained by reacting a chain polymer with a crosslinking agent; the chain polymer includes an aromatic group and a nitrogen-containing heterocyclic group.
2. The electron beam photoresist composition according to claim 1, characterized in that The aromatic group and the nitrogen-containing heterocyclic group are both located on the main chain of the chain polymer. Preferably, the chain polymer is a polyester based polymer. Preferably, the chain polymer is polymerized by at least one compound containing an aromatic group and at least one compound containing a nitrogen-containing heterocyclic ring. For example, the chain polymer is polymerized by one compound containing an aromatic group and two compounds containing a nitrogen-containing heterocyclic ring. Preferably, in the chain polymer, the polymer units are linked via ester bonds to form the polymer. Preferably, the aromatic group is a monocyclic or polycyclic aromatic or heteroaromatic group, for example, C 6-20 Aryl, 5-20 membered heteroaryl; preferably C 6-14 Aryl, 5-14 membered heteroaryl, for example, phenyl, naphthyl, anthracenyl or biphenyl. Preferably, the compound containing an aromatic group also includes a carboxyl group, a carboxylate group (such as COOC 1-12 alkyl), a carboxylic anhydride group, or a hydroxyl group. Preferably, the compound containing an aromatic group further comprises at least two groups selected from carboxylic acid, carboxylic acid ester, carboxylic acid anhydride, and / or at least two hydroxyl groups. Preferably, the compound containing a nitrogen-containing heterocyclic ring further comprises a carboxyl group, a carboxylate group, a carboxylic acid anhydride group, or a hydroxyl group. Preferably, the compound containing a nitrogen-containing heterocycle further comprises at least two groups selected from carboxylic acids, carboxylates, carboxylic anhydrides, and / or at least two hydroxyl groups.
3. The electron beam photoresist composition according to claim 1 or 2, characterized in that: The compound containing an aromatic group has a structure shown in the following M1': ROOC-A-COOR M1’ Wherein, A is selected from the following groups which are unsubstituted or optionally substituted by one, two or more Rs: C 6-20 Aryl, 5-20 membered heteroaryl, C 6-20 Aryl-C 6-20 Aryl or 5-20 membered heteroaryl-5-20 membered heteroaryl; Rs is selected from oxo, halogen, cyano, nitro, C 1-12 Alkyl, C 1-12 Alkoxy, C 3-12 Cycloalkyl or 3-12 membered heterocyclic group; R is selected from C 1-12 alkyl. Preferably, in M1', A is selected from C 6-14 Aryl, 5-14 membered heteroaryl, C 6-14 Aryl-C 6-14 Aryl or 5-14 membered heteroaryl-5-14 membered heteroaryl; R is selected from H, C 1-6 alkyl. Preferably, the compound containing an aromatic group is, for example, the following compound: Preferably, the compound containing a nitrogen-containing heterocycle is a compound of the following general formula I: Wherein, R1 and R2 are the same or different and are selected from -C 1-12 Alkyl-OR4, -C 1-12 Alkyl-COOR5, -C 1-12 Alkyl-OCOR5; R3 is selected from -C 1-12 Alkyl-OR4, -C 1-12 Alkyl-COOR5, -C 1-12 Alkyl-OCOR5, R6; R4, R5, R6 are the same or different and are selected from H, optionally replaced by one or more R a Substituted with the following groups: C 1-12 Alkyl, C 2-12 Alkenyl, C 2-12 Alkynyl, aryl, heteroaryl; R a are the same or different and are selected from oxo, halogen, cyano, nitro, alkyl, cycloalkyl, heterocyclyl, aryl, heteroaryl, -NR b R c 、-OR d 、-CO-R d 、-COOR d 、-SR e 、-SO-R e 、-SO2-R e ; R b , R c same or different, independently selected from hydrogen or optionally replaced by one, two or more R a Substituted with the following groups: C 1-12 Alkyl, C 3-12 Cycloalkyl; R d , R e The same or different, independently selected from H, or optionally replaced by one, two or more R a Substituted with the following groups: C 1-12 Alkyl, C 3-12 Cycloalkyl, 3-12 membered heterocyclic group. Preferably, the compound containing a nitrogen-containing heterocycle includes the compounds represented by the following M2' and M3': Among them, R 21 , R 22 , R 23 The same or different, independently selected from -C 1-12 Alkyl-OH; R 31 , R 32 The same or different, independently selected from -C 1-12 Alkyl-COOH or -C 1-12 Alkyl-COOC 1-12 Alkyl; R 33 Selected from H, C 1-12 Alkyl, aryl, heteroaryl, -C 1-12 Alkyl-OH, -C 1-12 Alkyl-OC 1-12 Alkyl, -C 1-12 Alkyl-COOH or -C 1-12 Alkyl-COOC 1-12 alkyl. Preferably, R 21 , R 22 , R 23 The same or different, independently selected from -C 1-6 Alkyl-OH; R 31 , R 32 The same or different, independently selected from -C 1-6 Alkyl-COOH or -C 1-6 Alkyl-COOC 1-6 Alkyl; R 33 Selected from H, C 1-6 Alkyl, -C 1-6 Alkyl-OH, -C 1-6 Alkyl-OC 1-6 Alkyl, -C 1-6 Alkyl-COOH or -C 1-6 Alkyl-COOC 1-6 alkyl. Preferably, the compound containing a nitrogen-containing heterocyclic ring is tris(2-hydroxyethyl)isocyanurate and tris(2-carboxyethyl)isocyanurate. Preferably, the chain polymer is a polymer obtained by reacting M1', M2' and M3'.
4. The electron beam photoresist composition according to any one of claims 1 to 3, characterized in that: The crosslinking agent is a crosslinkable compound having at least two substituents capable of forming crosslinks. Preferably, the crosslinking agent is an amino crosslinking agent, such as a glycoluril crosslinking agent, a melamine crosslinking agent, a urea crosslinking agent, a benzoguanamine crosslinking agent, or a phenolic compound having a substituent capable of forming a crosslink, such as hydroxymethyl and methoxymethyl. Preferably, the crosslinking agent is methoxymethylated glycoluril or methoxymethylated melamine, such as tetramethoxymethyl glycoluril, tetrabutoxymethyl glycoluril or hexamethoxymethyl melamine. Preferably, the cross-linking agent has a structure as shown in the following formula IC: Wherein, s is an integer from 1 to 12; R7 and R8 are the same or different and are independently selected from H, C 1-12 Alkyl, C 6-14 Aryl or 5-14 membered heteroaryl; R9, R 10 , R 11 , R 12 The same or different, independently selected from C 1-12 alkyl. Preferably, s is an integer from 1 to 6; Preferably, R7 and R8 are the same or different and are independently selected from H, C 1-6 Alkyl, phenyl; for example, H, methyl, ethyl, propyl, butyl or phenyl. Preferably, R9, R 10 , R 11 , R 12 The same or different, independently selected from C 1-6 The alkyl group is, for example, methyl, ethyl, n-propyl or n-butyl. Preferably, the cross-linking agent is selected from the following structures:
5. The electron beam photoresist composition according to any one of claims 1 to 4, characterized in that: The weight average molecular weight of the self-crosslinking resin is 1000-8000. Preferably, the molecular weight distribution coefficient of the self-crosslinking resin is less than 2.
5. Preferably, the self-crosslinking resin has the structural units shown below:
6. The electron beam photoresist composition according to any one of claims 1 to 5, characterized in that: The electron beam photoresist base resin material is a copolymer of an aromatic vinyl monomer and an α-halogenated acrylate monomer; Preferably, the aromatic vinyl monomer is selected from at least one of α-methylstyrene monomer and 4-fluoro-α-methylstyrene monomer. Preferably, the α-halogenated acrylate monomer is selected from at least one of α-methyl chloroacrylate monomer, α-ethyl chloroacrylate monomer, α-benzyl chloroacrylate monomer, α-chloroacrylate-1-adamantyl ester monomer, α-chloroacrylate-2,2,3,3,3-pentafluoropropyl monomer, α-chloroacrylate-2,2,3,3,4,4,4-heptafluorobutyl monomer, α-fluoroacrylate methyl monomer, α-fluoroacrylate ethyl monomer, α-fluoroacrylate benzyl ester monomer, α-fluoroacrylate-1-adamantyl ester monomer, α-fluoroacrylate-2,2,3,3,3-pentafluoropropyl monomer and α-chloroacrylate-2,2,3,3,4,4,4-heptafluorobutyl monomer. Preferably, the base resin material is a resin material obtained by copolymerization of α-methylstyrene and 2-methyl chloroacrylate as follows:
7. The electron beam photoresist composition according to any one of claims 1 to 6, characterized in that: The electron beam photoresist composition also includes a solvent; the solvent is selected from at least one of anisole, toluene, xylene, trimethylbenzene, chlorobenzene, dichlorobenzene, propylene glycol monoacetate, propylene glycol monoethyl ether, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol methyl ethyl ether, butyl acetate, neopentyl acetate, γ-butyrolactone and ethyl lactate. Preferably, the electron beam photoresist composition further comprises an auxiliary agent, and the auxiliary agent is selected from at least one of a surfactant, a photoacid generator, a thermal acid generator, a viscosity controller and a stabilizer.
8. The method for preparing the electron beam photoresist composition according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing the photoresist base resin material and the self-crosslinking resin to obtain the electron beam photoresist composition. Preferably, the method further comprises a process for preparing a self-crosslinking resin, comprising: S1. polymerizing a compound containing an aromatic group with a compound containing a nitrogen-containing heterocyclic ring to obtain a chain polymer; S2. reacting the chain polymer with a cross-linking agent.
9. A method for using the electron beam photoresist composition according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: coating the electron beam photoresist composition on a substrate, and sequentially performing pre-baking, exposure, post-baking, development and fixing to obtain a photolithography pattern.
10. Use of the electron beam resist composition according to any one of claims 1 to 7 in electron beam lithography.
Citation Information
Patent Citations
Method for producing polymer compound and polymer compound
CN104487484A
Organic bottom antireflective coating composition for nanolithography
CN105505146A
Method for removing metal ion impurity in polymer compound for photolithography
JP2010189563A
Coating compositions for use with an overcoated photoresist
US20070178406A1
